Auxiliary conductive agent, fluid dispersion, electrode, secondary battery, multilayer carbon nanotube powder, planar assembly, filter, electromagnetic wave-shielding and pellicle for extreme-ultraviolet light

Multi-wall carbon nanotube powders with specific tensile strength and angle of repose enhance conductivity and dispersibility, addressing the limitations of conventional conductive aids in electrodes and improving electrode performance.

JP2025010479AActive Publication Date: 2025-01-21SUMITOMO CHEM CO LTD

Patent Information

Application Number
JP2024058117
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-07
Filing Date
2024-03-29
Publication Date
2025-01-21
Estimated Expiration
2044-03-29

AI Technical Summary

Technical Problem

Conventional conductive aids in electrodes, such as carbon nanotubes, often fail to provide sufficient conductivity, and there is a need for improved dispersibility and conductivity in electrode materials.

Method used

The use of multi-wall carbon nanotube powders with specific tensile strength and angle of repose, ranging from 10 MPa to 100 MPa and 10 degrees to 90 degrees, respectively, to enhance conductivity and dispersibility in electrodes and other applications.

Benefits of technology

The multi-wall carbon nanotube powders improve conductivity and dispersibility, forming stable conductive paths within electrodes, leading to enhanced performance in secondary batteries and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010479000002
    Figure 2025010479000002
  • Figure 2025010479000001
    Figure 2025010479000001
Patent Text Reader

Abstract

To provide an auxiliary conductive agent excellent in an effect of improving conductivity, a fluid dispersion, an electrode, a secondary battery, a multilayer carbon nanotube powder, a planar assembly, a filter, an electromagnetic wave-shielding and a pellicle for extreme-ultraviolet light.SOLUTION: A multilayer carbon nanotube powder is a ground product of a multilayer carbon nanotube with a tensile strength of 10 to 100 MPa, and has a repose angle of 10 to 90 degrees. The multilayer carbon nanotube powder is included in an auxiliary conductive agent, a fluid dispersion, an electrode and a secondary battery. There are also provided a multilayer carbon nanotube powder, a planar assembly, a filter, an electromagnetic wave-shielding and a pellicle for extreme-ultraviolet light.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a conductive assistant, a dispersion, an electrode, a secondary battery, a multi-walled carbon nanotube powder, a planar aggregate, a filter, an electromagnetic wave shield, and a pellicle for extreme ultraviolet rays. [Background technology]

[0002] Carbon nanotubes (hereinafter sometimes referred to as "CNTs") have good mechanical and electrical properties, and are therefore expected to be used in a variety of applications. For example, Patent Document 1 focuses on the electrical conductivity and adhesion of electrode films in non-aqueous electrolyte secondary batteries (particularly lithium ion secondary batteries) and proposes the use of carbon nanotubes that satisfy predetermined physical properties (i.e., average outer diameter, BET specific surface area, fiber length, G / D ratio, volume resistivity, and true density) within predetermined ranges.

[0003] Secondary batteries such as lithium-ion secondary batteries are used as power sources in various fields such as mobile devices and electric vehicles. It is known that the electrode materials of secondary batteries include carbonaceous materials such as carbon black, ketjen black, fullerene, graphene, and CNT, and conductive assistants such as metal materials. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2021-95314 Summary of the Invention [Problem to be solved by the invention]

[0005] It has been known that carbonaceous materials such as carbon nanotubes are used as conductive assistants to improve the conductivity of electrodes. However, there are cases where electrodes using conventional conductive assistants do not achieve sufficient conductivity.

[0006] An object of one embodiment of the present disclosure is to provide a conductive assistant that is excellent in the effect of improving electrical conductivity. Another problem to be solved by another embodiment of the present disclosure is to provide a dispersion liquid, an electrode and a secondary battery, and a multi-walled carbon nanotube powder. The problem to be solved by yet another embodiment of the present disclosure is to provide a planar aggregate containing multi-walled carbon nanotube powder, a filter, an electromagnetic wave shield, and an extreme ultraviolet pellicle using the planar aggregate. [Means for solving the problem]

[0007] The present disclosure includes the following aspects. <1> A conductive assistant comprising a pulverized multi-walled carbon nanotube powder having a tensile strength of 10 MPa to 100 MPa and an angle of repose of 10 degrees to 90 degrees. <2> The maximum length of the multi-walled carbon nanotube is 10 μm to 30,000 μm. <1> The conductive assistant described in claim 1. <3> A conductive additive for the negative electrode, <1> or <2> The conductive assistant described in <4> <1> ~ <3> 13. A dispersion liquid comprising the conductive assistant according to any one of the above items and a dispersion medium. <5> An electrode active material; <1> ~ <3> and an electrode comprising the conductive assistant according to any one of the above. <6> <5> A secondary battery comprising the electrode according to claim 1. <7> A powder of multi-walled carbon nanotubes having a tensile strength of 10 MPa to 100 MPa and a maximum length of 1000 μm to 30000 μm, the powder having an angle of repose of 10 degrees to 90 degrees. <8> <7> A planar aggregate comprising the multi-walled carbon nanotube powder according to claim 1. <9> <8> A filter using the planar assembly described in . <10> <8> Electromagnetic wave shielding using the planar assembly described in 1. <11> <8> A pellicle for extreme ultraviolet light using the planar assembly described in claim 1. Effect of the Invention

[0008] According to one embodiment of the present disclosure, a conductive assistant having an excellent effect of improving electrical conductivity can be provided. According to another embodiment of the present disclosure, a dispersion liquid, an electrode and a secondary battery, and a multi-walled carbon nanotube powder can be provided. According to yet another embodiment of the present disclosure, it is possible to provide a planar aggregate containing multi-walled carbon nanotube powder, a filter, an electromagnetic wave shield, and a pellicle for extreme ultraviolet radiation using the planar aggregate. [Brief description of the drawings]

[0009] [Figure 1] 1 is a scanning electron microscope photograph showing one embodiment of an aggregate of multi-walled carbon nanotubes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] An example of an embodiment of the present disclosure will be described in detail below. The following description may be based on a representative embodiment of the present disclosure, but the present disclosure is not limited to such an embodiment, and can be modified as appropriate within the scope of the purpose of the present disclosure.

[0011] In the present disclosure, a numerical range indicated using "~" means a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when there are multiple substances corresponding to each component, the amount of each component means the total amount of the multiple substances, unless otherwise specified. In this specification, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved.

[0012] [Conductive assistant] The conductive assistant according to the present disclosure is a pulverized product of multi-walled carbon nanotubes having a tensile strength of 10 MPa to 100 MPa, and contains multi-walled carbon nanotube powder having an angle of repose of 10 degrees to 90 degrees.

[0013] In the present disclosure, a conductive assistant refers to a substance that coexists with an electrode active material (specifically, a positive electrode active material or a negative electrode active material) in an electrode formed using an electrode material, plays a role in assisting conductivity, and has the function of forming a conductive path.

[0014] The conductive assistant according to the present disclosure has an excellent effect of improving electrical conductivity. That is, the conductive assistant according to the present disclosure exhibits an excellent effect of forming a conductive path by coexisting with an electrode active material in an electrode. The reason for this is unclear, but it is presumed that the multi-walled carbon nanotube powder contained in the conductive assistant according to the present disclosure is a pulverized product of multi-walled carbon nanotubes having a tensile strength in a specific range, and the angle of repose is within the above range, so that the multi-walled carbon nanotubes, or the multi-walled carbon nanotubes and materials coexisting with the multi-walled carbon nanotubes in the electrode (e.g., electrode active material and other conductive materials) can easily maintain a state of contact with each other, and this, combined with the excellent electrical conductivity of the multi-walled carbon nanotube powder itself, forms a stable conductive path in the electrode.

[0015] In addition, carbon nanotubes tend to be difficult to disperse in a dispersion medium (e.g., water). However, a multi-walled carbon nanotube powder that is a pulverized product of multi-walled carbon nanotubes having a tensile strength in a specific range and has an angle of repose in the above range, in one embodiment, has excellent dispersibility in a dispersion medium. For this reason, it is presumed that when the multi-walled carbon nanotube powder is dispersed in a dispersion medium in the formation of an electrode, the dispersibility of the multi-walled carbon nanotube powder is improved, which in turn contributes to the formation of a stable conductive path in the electrode.

[0016] In this disclosure, "tensile strength" is measured with reference to the tensile test described in standard ISO 527-1. The tensile strength of the multi-walled carbon nanotubes according to the present disclosure (i.e., the tensile strength of the multi-walled carbon nanotubes before being pulverized into multi-walled carbon nanotube powder) is measured in a tensile state such as a sheet or thread.

[0017] In the present disclosure, multi-walled carbon nanotubes being in a sheet state means that an aggregate of multi-walled carbon nanotubes before being pulverized into multi-walled carbon nanotube powder has a sheet-like form. In the present disclosure, multi-walled carbon nanotubes being in a thread state means that an aggregate of multi-walled carbon nanotubes before being pulverized into multi-walled carbon nanotube powder has a fibrous form.

[0018] The tensile strength is measured by the following specific measuring method and conditions. When the multi-walled carbon nanotubes before crushing are in a sheet form, the sheet-like multi-walled carbon nanotube aggregate is cut into a piece of 75 mm x 10 mm to be used as a measurement sample, which is fixed to the gripping part of a tensile testing device (Shimadzu Corporation, Autograph AGS-X Series) and subjected to a tensile test at a speed of 1 mm / min. The breaking strength at which the measurement sample breaks is regarded as the tensile strength. When the multi-walled carbon nanotubes before crushing are in a thread form, the fibrous multi-walled carbon nanotubes are cut to a length of 500 mm to be used as a measurement sample, which is fixed to the gripping part of a tensile testing device (Shimadzu Corporation, Autograph AGS-X Series) and subjected to a tensile test at a speed of 1 mm / min using a fine wire gripper (Shimadzu Corporation). The breaking strength at which the measurement sample breaks is taken as the tensile strength. When the sheet-like measurement sample does not satisfy the above-mentioned size, or when the thread-like measurement sample does not satisfy the above-mentioned length, the measurement sample is used as it is to measure the tensile strength.

[0019] The tensile strength of the multi-walled carbon nanotube is 10 MPa to 100 MPa, preferably 30 MPa to 85 MPa, and more preferably 50 MPa to 70 MPa. When the tensile strength of the multi-walled carbon nanotube is 50 MPa or more, the multi-walled carbon nanotube is sufficiently long, so that the electrical conductivity of the multi-walled carbon nanotube is easily ensured. When the tensile strength of the multi-walled carbon nanotube is 70 MPa or less, the force required for crushing the sheet-like or thread-like multi-walled carbon nanotube is small, so that the multi-walled carbon nanotube can be easily processed.

[0020] The pulverization method for multi-walled carbon nanotubes having a tensile strength of 10 MPa to 100 MPa can be, for example, a freeze-pulverization method. The freeze-pulverization method is a processing method in which, whether the aggregate of multi-walled carbon nanotubes is in the form of a sheet or a thread, the aggregate of multi-walled carbon nanotubes is quenched with liquid nitrogen to eliminate the elasticity of the multi-walled carbon nanotubes and facilitate pulverization. Alternatively, pulverization may be performed by a known pulverization method such as a ball mill.

[0021] In this disclosure, the term "angle of repose" refers to the angle between the slope of a pile of powder and the horizontal plane when the pile of powder, which is dropped from a certain height onto a horizontal surface and deposited thereon, remains stable without collapsing spontaneously.

[0022] In the present disclosure, the angle of repose is measured by the injection method. The injection method is a method of measuring the angle of repose by depositing the powder to be measured on a measurement table having a disk-shaped upper surface. The injection method is not easily affected by the material of the measurement table, and the angle between the powder deposited in a cone shape and a horizontal plane (i.e., the angle of repose) can be easily measured using a measuring means such as a protractor. The angle of repose can also be measured using a commercially available measuring instrument. An example of a commercially available measuring instrument is the electromagnetic angle of repose measuring instrument AOR-57 (manufactured by Tsutsui Rikagaku Kikai Co., Ltd.).

[0023] The angle of repose can be adjusted by the shape (size, end shape, etc.) and particle size of the multi-walled carbon nanotubes.

[0024] In the conductive assistant according to the present disclosure, the angle of repose of the multi-walled carbon nanotube powder is 10 degrees to 90 degrees (i.e., 10 degrees or more and 90 degrees or less), and in one embodiment, the angle of repose is preferably 10 degrees or more and less than 40 degrees, more preferably 20 degrees or more and less than 40 degrees, and even more preferably 36 degrees or more and less than 40 degrees.

[0025] From the viewpoint of ensuring the fluidity of the multi-walled carbon nanotube powder to facilitate easy handling during production, and from the viewpoint of achieving good dispersibility in aqueous solvents, the angle of repose is preferably 10 degrees or more and less than 70 degrees, more preferably 10 degrees or more and less than 50 degrees, and particularly preferably 10 degrees or more and less than 34 degrees.

[0026] On the other hand, from the viewpoint of increasing the frictional force between the multi-walled carbon nanotube powder and making it easier to form a conductive path, the angle of repose is preferably 20 degrees or more and less than 90 degrees, more preferably 30 degrees or more and less than 85 degrees, and particularly preferably 36 degrees or more and less than 80 degrees.

[0027] In the conductive assistant according to the present disclosure, the multi-walled carbon nanotube powder has a bulk density of 0.001 g / cm3 or less from the viewpoint of improving dispersibility in an aqueous solvent. 3 ~0.19g / cm 3 is preferred, and 0.002 g / cm 3 ~0.1g / cm 3 More preferably, 0.005 g / cm 3 ~0.08g / cm 3 is more preferred. On the other hand, from the viewpoint of ease of introduction into aqueous solvents and ease of operation, the bulk density is set to 0.001 g / cm 3 More than 0.002 g / cm is preferable. 3 More preferably, 0.005 g / cm 3 The above is more preferable.

[0028] The bulk density of the multi-walled carbon nanotube powder is measured by tapped bulk density. Tapped bulk density refers to the bulk density measured after a measuring vessel filled with multi-walled carbon nanotube powder is dropped repeatedly 20 times from a height of 25 mm onto a hard surface.

[0029] In the conductive assistant according to the present disclosure, the multi-walled carbon nanotube powder has good electrical conductivity since the main component is carbon.

[0030] In the present disclosure, the electrical conductivity of the multi-walled carbon nanotube powder can be measured by the volume resistivity.

[0031] In the present disclosure, the volume resistivity of the multi-walled carbon nanotube powder pressed under the condition of 20 kN is 5.0 × 10 -2 When the electrical conductivity is Ω·cm or less, the multi-walled carbon nanotube powder can be judged to have excellent electrical conductivity.

[0032] The volume resistivity of the multi-walled carbon nanotube powder is 5.0×10 -2 It is preferable that the resistance is Ω·cm or less, and 1.0×10 -4 Ω cm~3.0×10 -2 Ω cm is more preferable, and 1.0×10 -4 Ω cm~2.0×10 -2 More preferably, it is 1.0×10 -4 Ω cm~2.0×10 -3 It is particularly preferred that the resistivity is Ω·cm.

[0033] The volume resistivity of the multi-walled carbon nanotube powder is measured by a four-probe method using a resistivity meter at 25° C. A Loresta device can be used as the resistivity meter. Specifically, multi-layer carbon nanotubes were measured using a Loresta device (product name: powder resistivity measurement system MCP-PD51, low resistivity meter Loresta-GP, low resistance probe for powder MCP-PD511 (constant current application method 4-probe method), all manufactured by Nitto Seiko Analytech Co., Ltd.). The tube powder is introduced into the resistivity measurement probe unit and pressed at 20 kN using the attached hydraulic pump. After the target load is reached, the volume resistivity (Ω·cm) is measured.

[0034] The conductive assistant according to the present disclosure is a pulverized product of multi-walled carbon nanotubes having a tensile strength of 10 MPa to 100 MPa, and is not particularly limited as long as it contains multi-walled carbon nanotube powder having an angle of repose of 10 degrees to 90 degrees. However, from the viewpoint of obtaining excellent conductivity, it is preferable that the multi-walled carbon nanotube powder is a pulverized product of multi-walled carbon nanotubes having a tensile strength of 10 MPa to 100 MPa and a maximum length of 10 μm to 30,000 μm.

[0035] The pulverization process for obtaining the pulverized product of multi-walled carbon nanotubes is not particularly limited, and any pulverization process capable of pulverizing the multi-walled carbon nanotubes into small pieces may be used.

[0036] The pulverization process may be a process in which the multi-walled carbon nanotubes are pulverized while still frozen. A pulverization device (e.g., a ball mill) is preferably used for the pulverization process. The pulverization device can be appropriately selected depending on the amount of multi-walled carbon nanotubes to be pulverized. For example, a ball mill "JFC-300" manufactured by Japan Analytical Industry Co., Ltd. can be used as the pulverization device.

[0037] The multi-walled carbon nanotubes to be subjected to the pulverization treatment may be an aggregate of multi-walled carbon nanotubes. The shape of the multi-walled carbon nanotubes to be subjected to the pulverization treatment may be, for example, a sheet (also called a mat), a thread, etc., and the sheet is preferable because it is not too hard and a large amount can be processed at one time.

[0038] One embodiment of the present disclosure includes a multi-walled carbon nanotube powder (hereinafter also referred to as "multi-walled CNT powder A") that is a pulverized product of multi-walled carbon nanotubes having a tensile strength of 10 MPa to 100 MPa and a maximum length of 1000 μm to 30000 μm and has an angle of repose of 10 degrees to 90 degrees. That is, the conductive assistant according to the present disclosure includes the multi-walled CNT powder A. In addition to being used as a conductive assistant, multi-walled CNT powder A can be used in a wide range of applications, including conductive inks, fillers for reinforcing resins, antistatic agents, and transparent conductive film materials.

[0039] Another embodiment of the present disclosure is a pulverized product of multi-walled carbon nanotubes including multi-walled carbon nanotubes having a maximum length of 1000 μm to 30000 μm, and includes a multi-walled carbon nanotube powder having a particle size distribution value (Dcnt) of 0.5 to 10 as shown in the following formula (1) (hereinafter also referred to as "multi-walled CNT powder B"). Particle size distribution value (Dcnt) = [Dn90 - Dn10] / Dn50 Equation (1) In formula (1), Dn90 is the number average particle size measured under the 90% criterion by placing crushed multi-walled carbon nanotubes in distilled water, leaving them for 3 hours, and then observing them using an optical microscope, Dn10 is the number average particle size measured under the 10% criterion, and Dn50 is the number average particle size measured under the 50% criterion.

[0040] The particle size distribution value (Dcnt) of the multi-walled CNT powder B is 0.5-10, preferably 1.1-10, and more preferably 2.0-10.

[0041] The pulverized material preferably simultaneously satisfies the particle size or average particle size of 100 to 30,000 μm and the strand diameter of 5 to 50,000 nm.

[0042] Multi-walled CNT powder B is a multi-walled carbon nanotube having a maximum length of 1000 μm to 30000 μm. Since the multi-walled CNT powder B is a pulverized product of multi-walled carbon nanotubes including nanotubes and has a particle size distribution value (Dcnt) of 0.5 to 10, it has excellent electrical conductivity and excellent dispersibility in a dispersion medium (for example, water). Carbon nanotubes tend to be difficult to disperse in a dispersion medium (for example, water), but since the particle size distribution value (Dcnt) is within the above range, the multi-walled CNT powder B has excellent dispersibility in a dispersion medium. For this reason, the multi-walled CNT powder B can be suitably used, for example, as a conductive assistant. That is, it is presumed that when applied as a conductive assistant, the multi-walled CNT powder B contributes to the formation of a stable conductive path in an electrode in combination with its own excellent electrical conductivity.

[0043] In addition to being used as a conductive assistant, multi-walled CNT powder B can be used in a wide range of applications, including conductive inks, fillers for reinforcing resins, antistatic agents, and transparent conductive film materials.

[0044] The multi-walled CNT powder C may have an angle of repose of 10 degrees to 90 degrees. In other words, the conductive assistant according to the present disclosure may contain the multi-walled CNT powder B having an angle of repose of 10 degrees to 90 degrees.

[0045] <Multi-walled carbon nanotubes> In the present disclosure, the multi-walled carbon nanotubes for obtaining the multi-walled carbon nanotube powder include multi-walled carbon nanotubes having a maximum length of 10 μm to 30,000 μm (preferably, 1,000 μm to 30,000 μm).

[0046] In the detailed explanation of "multi-walled carbon nanotubes" and "method for producing multi-walled carbon nanotubes" below, the terms "carbon nanotube," "single-walled carbon nanotube," "multi-walled carbon nanotube," and "multi-walled CNTs having a maximum length of 1000 μm to 30000 μm" may be abbreviated as "CNT," "SWCNT," "MWCNT," and "ULMWCNT," respectively.

[0047] ULMWCNT has a maximum length of 1000 μm to 30000 μm, which is longer than the general-purpose MWCNT and can take the form of fibers.

[0048] Here, the term "fiber" is generally used to refer to a structure in which one dimension is larger than the other two. The fibers may be thread-like fibers with a circular cross section, ribbon-like fibers with a rectangular cross section, hollow, or have other shapes. From the viewpoint of increasing electrical conductivity, the cross section of the ULMWCNT is preferably circular, and preferably hollow.

[0049] By taking on a fibrous shape, ULMWCNTs have the property of easily entangling with each other. The MWCN contains at least one ULMWCNT, and from the viewpoint that the MWCNTs are easily entangled with each other to form a more stable aggregate, it is preferable that the MWCN is an aggregate containing multiple ULMWCNTs. Hereinafter, an aggregate containing ULMWCNTs may be abbreviated as "ULMWCNT aggregate."

[0050] The aggregate of MWCNTs may be an aggregate having a three-dimensional structure in which the MWCNTs are entangled with one another. Fig. 1 is a scanning electron microscope (SEM) photograph showing one embodiment of an aggregate of MWCNTs according to the present disclosure. From the SEM photograph shown in Fig. 1, it can be seen that a plurality of fibrous ULMWCNTs are entangled to form an aggregate. Thus, the entangled state of the ULMWCNTs according to the present disclosure can be confirmed by SEM observation.

[0051] The length of ULMWCNTs can be measured by focusing on one ULMWCNT and observing multiple SEM images with adjacent viewing angles. indicates the measured length of the ULMWCNT in the longitudinal direction, and the maximum value among the measured lengths is taken as the "maximum length." When observing an SEM photograph, if one MWCNT with a maximum length in the range of 1000 μm to 30000 μm is observed within the viewing angle of the SEM photograph, it can be confirmed that the observed MWCNT includes ULWMCNT.

[0052] It is preferable that a plurality of ULMWCNTs are present within the viewing angle of the SEM photograph. Focusing on 100 MWCNTs included in the viewing angle of the SEM photograph, the maximum length of each is measured, and from the viewpoint of further improving the stability of the MWCNT aggregate due to the entanglement of the ULMWCNTs, it is preferable that 10% or more of the observed MWCNTs (i.e., ULMWCNTs) have a maximum length in the range of 1000 μm to 30000 μm, calculated as a number, be present, more preferably 20% or more, even more preferably 30% or more, and particularly preferably 50% or more.

[0053] The diameter of ULMWCNT can be measured by observing SEM or transmission electron microscope (TEM) photographs. Here, the diameter refers to the length in the direction perpendicular to the longitudinal direction of the ULMWCNT, and the diameter is measured at 10 different points on one ULMWCNT, and the average value is the diameter of that ULMWCNT.

[0054] The length of the ULMWCNT is in the range of 1000 μm to 30000 μm, preferably in the range of 1050 μm to 25000 μm, more preferably in the range of 1100 μm to 20000 μm, further preferably in the range of 1200 μm to 18000 μm, and particularly preferably in the range of 1300 μm to 15000 μm. The diameter of the ULMWCNT is preferably 1 nm to 100 nm, more preferably in the range of 2 nm to 80 nm, further preferably in the range of 3 nm to 50 nm, and particularly preferably in the range of 5 nm to 30 nm.

[0055] The length / diameter ratio of the ULMWCNT, so-called aspect ratio, is preferably 1,000 or more, more preferably 3,000 or more, further preferably 5,000 or more, and particularly preferably 10,000 or more. The aspect ratio can be calculated from the ratio of the maximum length to the diameter of one ULMWCNT. From the viewpoint of measurement accuracy, it is preferable to use the average value of the measurements of 20 or more ULMWCNTs.

[0056] From the viewpoint of dispersibility, the specific gravity of the ULMWCNT aggregate is preferably in the range of 1.5 to 2.5, more preferably in the range of 1.7 to 2.4, and further preferably in the range of 1.8 to 2.2. The specific gravity of the ULMWCNT aggregate can be measured by the method described in JIS Z8807:2012 "Method of measuring density and specific gravity of solids."

[0057] The purity of the ULMWCNT aggregate as MWCNT can be measured by thermogravimetric analysis. For example, a thermogravimetric (TG) curve and a differential thermal analysis (DTA) curve of the ULMWCNT aggregate are obtained using a thermal analyzer (Shimadzu Corporation, DTG-60). The largest exothermic peak in the DTA curve, which has a peak top at about 650°C to 750°C, is the combustion of MWCNT, and the other exothermic peaks are the combustion of substances other than MWCNT. The purity of MWCNT is obtained from the weight loss rate of the TG curve. From the viewpoint of the obtained electrical conductivity, the purity of the ULMWCNT aggregate is preferably 50% by mass or more, more preferably 65% ​​by mass or more, even more preferably 80% by mass or more, and particularly preferably 95% by mass or more.

[0058] ULMWCNT may contain 0.01% by mass to 50% by mass of Fe atoms derived from the iron catalyst used during production. ULMWCNT may contain Fe atoms, for example, in a state where they are adsorbed on the surface of the ULMWCNT, or in a state where they are incorporated inside the fibrous ULMWCNT formed during production.

[0059] The resulting fibrous ULMWCNTs are preferably flexible and strong. In addition, the conductivity of the ULMWCNT itself is 5000Ω. -1 m -1 It is preferable that the number of the electrodes is equal to or larger than 10,000. -1 m -1 More preferably, the electrical conductivity of the ULMWCNT itself is 1,000,000 Ω or more. -1 m -1The following is the result.

[0060] <Method of manufacturing multi-walled carbon nanotubes> The method for producing MWCNTs (i.e., MWCNTs including ULMWCNTs) in the present disclosure is not particularly limited.

[0061] As a method for producing MWCNT in the present disclosure, a conventionally known chemical vapor deposition (CVD) method, a method in which a gaseous reactant containing a carbon source is reacted in the presence of a catalyst, or the like can be used.

[0062] The MWCNTs in the present disclosure can be produced, for example, by referring to the production method described in JP 2016-102047 A. Hereinafter, the method for producing MWCNTs according to the present disclosure will be described with reference to an example, however, the method for producing MWCNTs according to the present disclosure is not limited to the following example.

[0063] An example of a method for producing MWCNTs in the present disclosure is the method described in JP 2016-102047 A, i.e., a method comprising the steps of passing a gaseous reactant containing one or more carbon sources into a reactor, reacting the one or more gaseous reactants in a reaction zone of the reactor in the presence of a catalyst to form product particles containing carbon, agglomerating the product particles into agglomerates, and applying a force to the agglomerates to continuously move the agglomerates out of the reaction zone (hereinafter also referred to as "production method X"). According to the production method X, MWCNTs, including ULMWCNTs, can be obtained in the form of fibrous aggregates or other aggregate forms that are easy to handle.

[0064] In the manufacturing method X, the force applied to the product particles may be a mechanical force. When the agglomerates are fibrous MWCNTs, the mechanical force applied to the product particles can be exerted by a rotating spindle around which the agglomerates are wound. The fibrous CNTs can be collected on the spindle or can be accumulated elsewhere by successively unwinding the spindle after one or more revolutions around the spindle.

[0065] The spindle is preferably oriented with the spindle axis perpendicular or parallel to the flow direction of the gaseous reactant(s), but may be oriented at other orientations, for example a spindle with the spindle axis oriented at an angle of 25° to the flow direction of the gaseous reactants may also be suitable for applying mechanical forces to the product particles.

[0066] The spindle can rotate about two axes (e.g., two perpendicular axes). In particular, the spindle can rotate about axes perpendicular and parallel to the flow direction of the gaseous reactants. Such a spindle can pull and twist the fibrous CNT aggregates to control the number and length of twists.

[0067] The spindle may be made of metal, ceramic, or plastic. The spindle can have different suitable shapes depending on the material properties and the intended use of the MWCNTs. It can be used as a mold for manufacturing objects. The preferred shape of the spindle is a rod shape or a box shape.

[0068] Fibrous MWCNTs are deposited on a spindle or elsewhere, and the coating thickness and its orientation can be controlled by controlling the reaction time and conditions, or by the conditions under which an electric or other field is applied to the carbon product. The coating thickness and orientation of the carbon product can be controlled, for example, by gas flow forces.

[0069] The rotation speed of the spindle is preferably 0.01 rpm (revolutions / minute; the same applies below) to 10,000 rpm, and more preferably 0.1 rpm to 100 rpm. The spinning speed (i.e., the rotational speed of the spindle) may be adjusted so that the material is collected at a similar rate as it is produced. The rotational speed of the spindle may control the thickness of the accumulated MWCNT filaments. In a preferred embodiment, as the spindle rotates, the MWCNT filaments are processed in the axial direction of the spindle, such that the MWCNT filaments are wrapped evenly along the spindle, rather than only at one particular point on the spindle.

[0070] The MWCNT fibers may be collected, for example, on the reactor wall by a substrate placed in the reactor. The substrate may be a fixed substrate or a rotating guide that is used to apply a strong and equal force to the MWCNT fibers as they are collected. Suitable substrate configurations for fiber technology include a substrate consisting of two guides positioned at right angles to each other.

[0071] In process X, the mechanical force applied to the product particles may be a force applied by an accelerating gas flow. The accelerating gas flow may be generated by passing the product particles through a reactor having a narrow diameter or through a capillary tube downstream of the reaction zone. A vacuum may be applied to the product particles.

[0072] Other forces that can be applied to the product particles include electrostatic forces, suitably applied by a charged plate. Electrostatic forces require that the product particles be charged. The use of a charged plate allows the MWCNTs to be produced in the form of an intertwined mat on the charged plate.

[0073] Other forces applied to the product particles may also be magnetic forces or photon pressure applied by a light source.

[0074] The CNT source may be injected in the form of a liquid containing a carbon source instead of a gaseous reactant containing a carbon source. When a liquid is used as the CNT source, it can be injected through a single inlet or multiple inlets, for example in a showerhead arrangement.

[0075] The gaseous reactant or reactants are preferably reacted at between 500° C. and 1600° C., more preferably between 1000° C. and 1500° C. or 1600° C. (particularly between 1000° C. and 1500° C.). A temperature gradient is preferably maintained within the reactor, with the reaction zone being maintained at a higher temperature than the product zone of the reactor.

[0076] The gaseous reactants may be mixed with one or more gases that act as diluents. The gaseous reactants may be mixed with gases that do not play a direct role in the reaction but play a supporting role. It is also preferred to use a diluent gas that can react with the amorphous carbon by-product to keep the reactive sites on the catalyst intact to produce nanotubes.

[0077] Examples of gases that can be used as a diluent include argon or other inert gases, hydrogen, nitrogen, ammonia, carbon dioxide, and helium. Among these, hydrogen is particularly preferred as a gas that can be used as a diluent. The flow rate of the gas as a diluent is preferably 2000 mL (milliliters) / min or less, and more preferably 400 mL / min to 800 mL / min.

[0078] The gas pressure of the gaseous reactants and any diluents is preferably between 0.1 bar and 50 bar, more preferably between 0.5 bar and 5 bar, and even more preferably between 1 bar and 2 bar. In case of gas effluent from the furnace, the effluent gas can be recycled with or without cleaning.

[0079] The composition of the product particles can be controlled by monitoring the agglomerates and changing the reaction conditions based on the information obtained. For example, the agglomerates can be monitored by online Raman spectroscopy, which provides data indicative of single-walled or multi-walled CNTs. It also provides data indicative of the diameter and crystallinity of the CNTs. The agglomerates can also be monitored by online conductivity measurements, gas analysis, measuring the opacity of the reaction zone and / or measuring the winding force.

[0080] When the agglomerates are removed from the reactor, it is preferable to prevent air from entering the reactor, which is particularly important when the diluent gas contains hydrogen, for example to prevent an explosive mixture of hydrogen and air from forming in the reactor.

[0081] The product particles in production method X contain ULMWCNTs. Depending on the production conditions, SWCNTs may also be contained in addition to MWCNTs.

[0082] The product particles may be produced by chemical vapor deposition, where a gaseous reactant, a carbon source, is reacted in the presence of a catalyst.

[0083] Carbon-containing compounds suitable as carbon sources include, for example, carbon monoxide, carbon dioxide, aromatic hydrocarbons (e.g., benzene, toluene, xylene, cumene, ethylbenzene, naphthalene, or mesitylene), non-aromatic hydrocarbons (e.g., methane, ethane, propane, butane, pentane, hexane, cyclohexane, ethylene, propylene, or acetylene), and oxygen-containing hydrocarbons (e.g., formaldehyde, acetaldehyde, acetone, methanol, ethanol, diethyl ether, polyethylene glycol, 1-propanol, ethyl formate, and hydrocarbons including mixtures of two or more thereof). The carbon-containing compound is preferably carbon monoxide, methane, ethylene or acetylene.

[0084] The carbon source preferably contains oxygen. Ethanol is a particularly preferred carbon source. Oxygen can be introduced into the reactor by other methods, such as by using a diluent gas or a carbon source containing water.

[0085] The gaseous reactant that is the carbon source is preferably injected into the reactor at a rate of 0.01 mL / min to 10 mL / min, more preferably 0.08 mL / min to 0.25 mL / min.

[0086] The catalyst is preferably a transition metal, particularly chromium (Cr), molybdenum (Mo), tungsten (W) or VIIIB transition metal. Specifically, the catalyst may be, for example, iron (Fe), cobalt (Co), nickel (Ni), ruthenium (Ru), rhodium (Rh), palladium (Pd), osmium (Os), iridium (Ir) or prism. Preferred are platinum (Pt) or manganese (Mn), or mixtures thereof. Metals from the lanthanide and actinide series, such as yttrium (Y), may also be used as catalysts. More preferred are Fe, Ni, Co, Mo, and mixtures thereof, such as a mixture of Ni and Co (mass ratio: 50 / 50), a mixture of Fe and Ni, or a mixture of Fe and Mo. Any of these transition metals may be used alone or in combination with any of the other transition metals listed to act as a catalyst for CNT growth, with it being particularly preferred that the catalyst is a mixture of two or more of the metals listed.

[0087] The catalyst is preferably formed by decomposition of a precursor. The precursor is preferably a thermally, photo- or plasma-decomposable compound of one or more of the above metals, such as a carbonyl or cyclopentadienyl organometallic compound. Ferrocene, iron pentacarbonyl, nickelocene and cobaltocene are particularly preferred precursors. Suitably, at least 0.01% by weight of the precursor is contained in the carbon source, and preferably 0.2% to 2.5% by weight of the precursor is contained in the carbon source. In one embodiment, 0.23% to 2.3% by weight of the precursor is contained in the carbon source. The catalyst may be used supported on a carrier, and preferred carriers include silica and magnesium oxide.

[0088] The carbon source is preferably reacted in the presence of a promoter. Suitable promoters are one or more of sulfur, phosphorus, molybdenum and organic compounds of these elements. Thiophene is also one of the preferred promoters. Suitably, up to 10% by weight (10% by weight or less) of the promoter is included in the carbon source. Preferably, 0.2% to 6% by weight of the promoter is included in the carbon source. When high or low concentrations of thiophene are used as the promoter, MWCNTs are formed. For example, MWCNTs are well formed using ethanol containing 0 mass % or 1.5 mass % to 4.0 mass % thiophene and 1.0 mass % to 10.0 mass % (particularly 2.3 mass %) ferrocene, with an injection rate of 5.0 mL / hour to 30.0 mL / hour (particularly 7.5 mL / hour), a hydrogen flow rate of 400 mL / min to 800 mL / min, and a synthesis temperature of 1100°C to 1180°C.

[0089] According to the production method X, it is possible to obtain fibrous CNTs having a length of at least 500 μm, for example, at least 1 mm. The fibrous CNTs can take the form of a thread or a mat. The length of the fibrous CNTs can be controlled, for example, by the winding capacity of a spindle used in producing the fibrous CNTs.

[0090] The manufacturing method X preferably includes a step of reacting a carbon source in a reaction zone of a reactor to generate CNTs, and a step of aggregating the CNTs into aggregates by applying a force to the CNTs. According to this manufacturing method, fibrous CNTs can be easily manufactured.

[0091] In another embodiment, the MWCNTs comprising ULMWCNTs may be produced in a reaction zone by the methods described above, followed by condensation to form MWCNTs comprising ULMWCNTs, and continuously withdrawing the MWCNTs from near the reaction zone. In another embodiment, the method may include producing MWCNTs containing ULMWCNTs in a reaction zone, continuously electrostatically attracting the MWCNTs containing ULMWCNTs from the reaction zone, and recovering the MWCNTs containing ULMWCNTs.

[0092] The above manufacturing method X is just one example, and the manufacturing method of MWCNTs, including ULMWCNTs, is not limited to the above.

[0093] The conductive assistant according to the present disclosure is preferably contained in an electrode, is preferably contained in an electrode included in a secondary battery, and is preferably contained in a negative electrode included in a secondary battery. The conductive assistant according to the present disclosure is preferably a conductive assistant for a negative electrode. The electrodes and secondary batteries to which the conductive assistant according to the present disclosure can be applied will be described later.

[0094] [Dispersion] The dispersion according to the present disclosure contains the conductive assistant according to the present disclosure and a dispersion medium. The dispersion according to the present disclosure has good dispersibility of the conductive assistant according to the present disclosure in the dispersion medium, and has excellent electrical conductivity. The dispersion according to the present disclosure is preferably used to form an electrode.

[0095] <Conductive additive> The conductive assistant contained in the dispersion according to the present disclosure is the same as the conductive assistant according to the present disclosure described above, and therefore a description thereof will be omitted here.

[0096] <Dispersion medium> The dispersion medium preferably contains water, and more preferably contains water as a main component. "Containing water as a main component" means that the proportion of water in the dispersion medium is more than 50% by mass. The proportion of water in the dispersion medium is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 99% by mass or more, and may be, for example, 100% by mass.

[0097] The water is not particularly limited, but is preferably distilled water, ion-exchanged water, pure water, or the like, which contains fewer impurities.

[0098] The dispersion medium may be a mixture of water and a hydrophilic solvent. Examples of hydrophilic solvents include carbonate compounds such as ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, and butylene carbonate; ether compounds such as tetrahydrofuran; ketone compounds such as acetone; lower alcohol compounds such as methanol and ethanol; and acetonitrile. When the dispersion medium contains a hydrophilic solvent, the proportion of the hydrophilic solvent in the dispersion medium is preferably 10 mass % or less, more preferably 5 mass % or less, and even more preferably 1 mass % or less.

[0099] The dispersion may further contain other components that can be used in the dispersion in addition to the conductive assistant and dispersion medium according to the present disclosure. Examples of other components include dispersants, antifoaming agents, antistatic agents, conductive assistants other than the conductive assistant according to the present disclosure, etc. Furthermore, the composition may further contain a trace amount of impurity components, so-called inevitable impurities, etc.

[0100] <Dispersant> The dispersion may contain a dispersant for the purpose of further improving the dispersibility and dispersion stability of the conductive assistant. The dispersant is not particularly limited, and examples thereof include various surfactants. Examples of the dispersant also include polymer compounds such as resins. The dispersant is preferably a surfactant. The surfactant may be an ionic surfactant or a nonionic surfactant, and is not particularly limited. The surfactants can be used alone or in combination of two or more.

[0101] Examples of ionic surfactants include anionic surfactants and cationic surfactants. and amphoteric surfactants. Examples of the anionic surfactant include aromatic sulfonic acid surfactants such as alkylbenzene sulfonates (e.g., dodecylbenzene sulfonate) and dodecylphenyl ether sulfonate; ether sulfate surfactants; phosphate surfactants; and carboxylic acid surfactants. Examples of the cationic surfactant include alkylamine salts and quaternary ammonium salts. Examples of the amphoteric surfactant include alkyl betaine surfactants and amine oxide surfactants. As the ionic surfactant, an ionic surfactant having an aromatic ring (so-called aromatic ionic surfactant) is preferred, and aromatic sulfonic acid surfactants such as alkylbenzene sulfonate and dodecyl phenyl ether sulfonate are more preferred. Aromatic ionic surfactants tend to be excellent in dispersibility, dispersion stabilization, and concentration of multi-walled carbon nanotubes.

[0102] Examples of nonionic surfactants include sugar ester surfactants such as sorbitan fatty acid esters and polyoxyethylene sorbitan fatty acid esters; fatty acid ester surfactants such as polyoxyethylene resin acid esters and polyoxyethylene fatty acid diethyl esters; ether surfactants such as polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers and polyoxyethylene polypropylene glycols; and aromatic nonionic surfactants such as polyoxyalkylene octyl phenyl ether, polyoxyalkylene nonyl phenyl ether, polyoxyalkyl dibutyl phenyl ether, polyoxyalkyl styryl phenyl ether, polyoxyalkyl benzyl phenyl ether, polyoxyalkyl bisphenyl ether, polyoxyalkyl cumyl phenyl ether and polyoxyalkylene phenyl ether. As the nonionic surfactant, an ionic surfactant having an aromatic ring (so-called aromatic nonionic surfactant) is preferable, polyoxyalkylene phenyl ether is more preferable, and polyoxyethylene phenyl ether is further preferable. Aromatic nonionic surfactants tend to be excellent in dispersibility, dispersion stabilization, and concentration of multi-walled carbon nanotubes.

[0103] Other dispersants that are excellent in dispersibility, dispersion stability, and high concentration of multi-walled carbon nanotubes include β-naphthalenesulfonic acid formalin condensate sodium salts, such as Demol N, Demol RN, and Demol T (manufactured by Kao Corporation), polyoxyethylene stearyl ether, Brij S 100 (manufactured by Sigma-Aldrich), polyvinylpyrrolidone K30 (e.g., manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), carboxymethylcellulose (CMC) (e.g., manufactured by Daicel Miraize Co., Ltd.), sodium deoxycholate (e.g., manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and SOLSPERSE. TM W100, SOLSPERSE TM W150 (manufactured by Lubrizol Japan, Inc.) etc. From the viewpoint of excellent dispersibility, dispersion stabilization ability and high concentration of multi-walled carbon nanotubes, CMC is particularly preferable.

[0104] When the dispersion liquid contains a dispersant, the amount of the dispersant used is not particularly limited and can be appropriately set depending on the type of dispersant, the amount of multi-walled carbon nanotubes, the amount of dispersion medium, and the like.

[0105] [Method for producing dispersion] The method for producing the dispersion is not particularly limited. The dispersion liquid can be produced by dispersing the conductive assistant according to the present disclosure in a dispersion medium. That is, the dispersion liquid according to the present disclosure can be produced by a method including a step of dispersing the conductive assistant according to the present disclosure in a dispersion medium (also referred to as a "dispersion step"). The dispersion medium that can be used in the dispersion step is as described above.

[0106] The dispersion method is not particularly limited. Examples of the dispersion method include methods using a dispersion device such as a stirrer, a homogenizer, a colloid mill, a flow jet mixer, a dissolver, a paint conditioner, a Manton emulsifier, a jet mill, or an ultrasonic device. Examples of the dispersion method include methods using known pulverization means, such as ball milling (e.g., ball mill, vibration ball mill, planetary ball mill, bead mill, etc.), sand milling, colloid milling, jet milling, roller milling, and dispersing machines such as vertical or horizontal agitator mills, attritors, colloid mills, three-roll mills, pearl mills, super mills, impellers, dispersers, KD mills, dynatrons, and pressure kneaders. As a dispersion method, a method using a jet mill is preferable, and a method using a wet jet mill is more preferable. A wet jet mill is a dispersion device that pressure-feeds a mixture in a solvent as a high-speed flow from a nozzle arranged in a sealed pressure-resistant container. In the wet jet mill, multi-walled carbon nanotubes are dispersed in a pressure-resistant container by collisions between opposing flows, collisions with the container wall, turbulence caused by high-speed flows, shear flows, and the like. As a wet jet mill, an ultra-high pressure homogenizer (models: NAGS20, NAGS100, JAGS200, NAGS1000, etc.) manufactured by Jokou Corporation can be suitably used. However, the wet jet mill is not limited to this. When the above-mentioned ultra-high pressure homogenizer is used as the dispersing device, the dispersion treatment pressure is preferably 10 MPa to 250 MPa.

[0107] The method for producing the dispersion may include a step of drying the multi-walled carbon nanotube powder, which is the conductive assistant according to the present disclosure, prior to the above-mentioned dispersion step (also referred to as a "drying step").

[0108] When moisture is attached to the multi-walled carbon nanotubes, the multi-walled carbon nanotubes tend to adhere to each other due to the surface tension of the water, which may lead to a decrease in dispersibility. Therefore, by performing a drying process of the conductive assistant body before the dispersion process, moisture attached to the multi-walled carbon nanotube powder is removed, and adhesion between the multi-walled carbon nanotubes due to moisture adhesion is suppressed, thereby further improving the dispersibility of the multi-walled carbon nanotubes in the dispersion medium according to the present disclosure. The drying method is not particularly limited. Examples of the drying method include heat drying, vacuum drying, and heat vacuum drying. The drying method is preferably heated vacuum drying. The drying temperature is not particularly limited, and is preferably from 40°C to 100°C, for example. The drying time is not particularly limited, and can be appropriately set depending on the drying temperature, the degree of moisture adhesion to the multi-walled carbon nanotubes in the present disclosure, and the like.

[0109] An example of the production of a dispersion liquid is shown below, but the production of the dispersion liquid according to the present disclosure is not limited to the following.

[0110] <Production Example 1: Example of production of dispersion liquid> The conductive assistant according to the present disclosure (e.g., 0.040 g) is weighed and placed in a three-neck flask. After the conductive assistant is placed in the flask, a large excess of ion-exchanged water as a dispersion medium is poured into the flask (e.g., 20 mL) and stirred at room temperature (25°C, the same applies below). At this time, a known dispersant (e.g., carboxymethylcellulose) may be added as appropriate. Next, the conductive assistant is dispersed in the dispersion medium using a known dispersion device (e.g., an ultrasonic irradiation device or a wet jet mill). The obtained dispersion liquid is further stirred with a stirrer at room temperature for a long period of time (e.g., 1 hour to 48 hours). In this manner, the dispersion liquid according to the present disclosure is obtained.

[0111] It should be noted that a dispersion containing the multi-walled CNT powder A or multi-walled CNT powder B and a dispersion medium can also be used. Details of the components that the dispersion can contain and the method for producing the dispersion can be found by replacing the conductive assistant according to the present disclosure with the multi-walled carbon nanotube powder of aspect A or aspect B in the above description of the dispersion according to the present disclosure and the method for producing the dispersion.

[0112] [Electrodes and secondary batteries] The electrode according to the present disclosure includes an electrode active material and a conductive assistant according to the present disclosure. The secondary battery according to the present disclosure includes the electrode according to the present disclosure. The electrode according to the present disclosure contains the conductive assistant according to the present disclosure, and therefore has excellent conductive path formation properties within the electrode, and therefore the secondary battery according to the present disclosure has excellent cycle characteristics. Hereinafter, an embodiment of an electrode and a secondary battery including the electrode will be described.

[0113] <Electrode> The electrode may include the conductive assistant according to the present disclosure. The conductive assistant included in the electrode is the same as the conductive assistant according to the present disclosure, and therefore, hereinafter, a description of the conductive assistant will be omitted. The multi-walled CNT powder A or the multi-walled CNT powder B may be used as a conductive assistant (preferably, a conductive assistant for a negative electrode).

[0114] The electrode may be at least one of a positive electrode and a negative electrode. The electrode may include an electrode active material layer.The electrode may include a current collector and an electrode active material layer disposed on the current collector.

[0115] The current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, the current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver or the like. Specifically, a transition metal that easily adsorbs carbon, such as copper or nickel, may be used as the current collector.

[0116] The electrode active material layer may contain an electrode active material, which is preferably an electrode active material particle.

[0117] When the electrode is a positive electrode, the electrode active material particles are not particularly limited and may include a positive electrode active material that is commonly used in electrode materials for positive electrodes. Specifically, the positive electrode active material may be, for example, a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), a compound substituted with one or more transition metals, a lithium iron oxide such as LiFe3O4, or a lithium ferric oxide having the chemical formula Li 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2 Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B, and Ga, and satisfies 0.01≦c2≦0.66); 2-c3 M c3O2 (where M is at least any one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01 ≦ c3 ≦ 0.1), or Li2Mn3MO8 (where M is at least any one selected from the group consisting of Fe, Co, Ni, Cu, and Zn). Examples include lithium manganese composite oxides represented by these formulas, and LiMn2O4 in which a part of Li in the chemical formula is substituted with alkaline earth metal ions.

[0118] When the electrode is the negative electrode, the electrode active material is not particularly limited and can include electrode active materials commonly used for negative electrode materials. Specifically, the electrode active material can include graphite-based active material particles or silicon-based active material particles. As the graphite-based active material particles, one or more selected from the group consisting of artificial graphite, natural graphite, graphitized carbon fibers, and graphitized mesocarbon microbeads may be used. By using artificial graphite, the rate characteristics can be improved.

[0119] As the silicon-based active material particles, one or more selected from the group consisting of Si, SiOx (0 < x < 2), Si-C composites, and Si-Y alloys (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, transition metals, group 13 elements, group 14 elements, rare earth elements, and combinations thereof) may be used. By using silicon-based active material particles, the battery can be made to have a higher capacity.

[0120] The electrode active material layer may further include a binder. The binder is not particularly limited and may include binders commonly used in electrode materials. Examples of the binder include at least one polymer selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and polyacrylic acid, as well as polymers in which hydrogen atoms of these polymers are substituted with Li, Na, Ca, or the like.

[0121] <Secondary battery> The secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. At least one of the positive electrode and the negative electrode is preferably an electrode according to the present disclosure, and the negative electrode is preferably an electrode according to the present disclosure.

[0122] The separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move, and is not particularly limited as long as it is one that is usually used as a separator in a secondary battery. The separator preferably has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specific examples of the separator include porous polymer films. The porous polymer film may be, for example, a porous polymer film made from a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure in which two or more of these films are laminated. The separator may also be a normal porous nonwoven fabric, such as a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, or the like. In order to ensure heat resistance or mechanical strength, the separator may also be a coated separator containing a ceramic component or a polymeric substance. The separator may be selectively made into a single-layer or multi-layer structure.

[0123] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium ion secondary batteries, but are not limited to these.

[0124] Specifically, the electrolyte can include a non-aqueous organic solvent and a metal salt. Examples of non-aqueous organic solvents include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydroxyfuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphate triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0125] Among carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, are highly viscous organic solvents with high dielectric constants and good dissociation of lithium salts, and therefore can be preferably used as non-aqueous organic solvents. It is more preferable to use such cyclic carbonates as non-aqueous organic solvents by mixing them with linear carbonates having low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, since this makes it possible to obtain an electrolyte having high electrical conductivity.

[0126] The metal salt may be a lithium salt. The lithium salt is a substance that is easily dissolved in a non-aqueous electrolyte. The anion portion of the lithium salt may be, for example, F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - One or more types selected from the group consisting of:

[0127] In addition to the electrolyte constituents, such as the nonaqueous organic solvent and metal salt, the electrolyte may further contain one or more additives, such as a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the battery life characteristics, suppressing a decrease in battery capacity, and improving the battery discharge capacity.

[0128] The above-mentioned secondary battery can be configured into a battery module including the secondary battery as a unit cell and a battery pack including the battery module. The battery module and the battery pack can be used as a power source for a medium- to large-sized device selected from the group consisting of an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, and a power storage system.

[0129] An example of the production of an electrode and a secondary battery will be described below, but the production of an electrode and a secondary battery according to the present disclosure is not limited to the following.

[0130] <Production Example 2: Production Example of Electrode (Negative Electrode) and Secondary Battery> A slurry for the negative electrode is produced by mixing, in a predetermined mass ratio, artificial graphite known as a negative electrode active material, the dispersion according to the present disclosure and known carbon black as a negative electrode conductive assistant, and styrene butadiene rubber (SBR) known as a negative electrode binder and known carboxymethyl cellulose (CMC) with distilled water. The negative electrode slurry is applied to a negative electrode current collector (Cu), dried, and rolled to a final thickness ( That is, the total thickness of the current collector and the negative electrode active material layer is adjusted to prepare the negative electrode. Thereafter, the current collector coated with the negative electrode slurry is further dried in an oven to produce a negative electrode. Next, a known positive electrode slurry is applied to a positive electrode current collector (Al), dried, and rolled to adjust the final thickness (i.e., the total thickness of the current collector and the positive electrode active material layer) to prepare a positive electrode. As the positive electrode slurry, for example, the positive electrode slurry described in paragraph

[0096] of JP-A-2022-521422 can be used. A separator is interposed between the negative electrode and the positive electrode to produce a monocell, and an electrolyte is injected to produce a lithium ion secondary battery.

[0131] The cycle characteristics of a lithium ion secondary battery can be evaluated based on the capacity retention rate. Specifically, the lithium-ion secondary battery is subjected to a life evaluation at 45°C, with a fixed charge C-rate of 1.0C and a fixed discharge C-rate of 1.0C, and the capacity retention rate (%) after 100 cycles is evaluated. By using the conductive assistant according to the present disclosure, a conductive path is preferably established within the electrode, resulting in excellent cycle characteristics.

[0132] The planar aggregate according to the present disclosure includes the multi-walled carbon nanotube powder according to the present disclosure. The ratio of the multi-walled carbon nanotube powder according to the present disclosure contained in the planar aggregate according to the present disclosure is usually 1 mass% or more with respect to the total mass of the planar aggregate. The planar aggregate according to the present disclosure may include other components such as carbon nanotube powder (particularly multi-walled carbon nanotube powder) having a maximum length of less than 1000 μm.

[0133] [Method for producing planar assemblies] The method for producing the planar assembly according to the present disclosure is not particularly limited. The planar aggregate according to the present disclosure can be produced, for example, as a nonwoven fabric-like planar aggregate, by dispersing the multi-walled carbon nanotube powder according to the present disclosure, or the multi-walled carbon nanotube powder according to the present disclosure and other components, such as carbon nanotube powder having a maximum length of less than 1000 μm (particularly multi-walled carbon nanotube powder), in water or other fluid and filtering once or twice or more times.

[0134] One embodiment of the planar assembly according to the present disclosure includes, for example, a film.

[0135] The planar assemblies of the present disclosure are useful, for example, in filters, electromagnetic shields, and extreme ultraviolet (EUV) pellicles. EXAMPLES

[0136] The conductive assistant according to the present disclosure will be described in more detail below with reference to examples. The conductive assistant according to the present disclosure is not limited to the following examples as long as it does not deviate from the gist of the present disclosure.

[0137] Example 1 1. MWCNT1 Preparation As MWCNT1, "multi-walled carbon nanotubes" (catalog number: 901019, 50-90 nm diameter, >95% carbon basis, manufactured by Sigma-Aldrich) were prepared.

[0138] 2-1. Preparation of Dispersion 1 The following materials were mixed and pre-dispersed by processing for 1 hour using an Ace Homogenizer manufactured by Nippon Seiki Co., Ltd., to obtain pre-dispersion liquid 1. (Dispersion liquid composition) 1.1g of the MWCNT1 obtained above ·CARBOXYMETHYL CELLULOSE SODIUM SALT HIGH VISCOSITY (manufactured by MP Biomedicals) 1.65g ·Pure water 547.2g The above pre-dispersion liquid 1 was subjected to main dispersion using an ultra-high pressure homogenizer (model: NAGS100) manufactured by Joko Corporation as a wet jet mill, and thus dispersion liquid 1 was obtained. Nozzle diameter: 0.22mm Pressure: 85MPa Number of times: 8 Method: Circulation method

[0139] 2-2.Tensile strength Dispersion liquid 1 was poured onto a 22 mm × 75 mm × 3 mm glass slide-type silicon plate (Dosaka EM Co., Ltd., #08-1044), heated to 100°C and dried to prepare a measurement sample. The sample was then fixed to the gripping part of a tensile testing device (Shimadzu Corporation, Autograph AG-IS) and subjected to a tensile test at a speed of 1 mm / min. As a result, the tensile strength was 11.5 MPa.

[0140] 3. Maximum length When 100 MWCNTs were observed in multiple SEM photographs (magnification: 5000 times) of MWCNT1 adjacent to each other, the maximum length was 50 μm.

[0141] 4. Preparation of MWCNT Powder 1 MWCNT powder 1 was obtained by crushing MWCNT1 using a freezing crusher (Japan Analytical Industry Co., Ltd., JFC-2000). 5 g of MWCNT1 was placed in a 75 ml sample container, and one steel ball made of tungsten carbide was placed in the sample container, after which the sample container was attached to a crushing rod. The entire sample container was immersed in liquid nitrogen to cool MWCNT1 and the steel ball, and the crushing rod was then moved up and down to move the steel ball inside the sample container and crush MWCNT1. Freezing retention time: 5 minutes Grinding time: 2 minutes

[0142] 5. Measurement of angle of repose The angle of repose of the MWCNT powder 1 was measured by the above-mentioned injection method. A sufficient amount of the MWCNT powder 1 was piled up on a measuring table having a disk-shaped upper surface, and the angle between the powder piled up in a cone shape and the horizontal plane was measured with a protractor. As a result, the angle of repose was 35 degrees.

[0143] 6. Measurement of volume resistivity Using a Loresta device (product name: powder resistivity measurement system MCP-PD51, low resistivity meter Loresta-GP, low resistivity probe for powder MCP-PD511 (constant current application type 4-probe method), all manufactured by Nitto Seiko Analytech Co., Ltd.), MWCNT powder 1 was introduced into the powder resistivity measurement probe unit and pressed at 20 kN using the attached hydraulic pump. After the target load was reached, the volume resistivity (Ω·cm) was measured. As a result, the volume resistivity was 9.2 × 10 at 20 kN. -3 The value was Ω·cm.

[0144] Example 2 1. Preparation of MWCNT2 Containing ULMWCNT MWCNT2 containing ULMWCNT was prepared by a floating catalyst method (CVD method) that directly interacts with the self-assembly of CNT bundles in the gas phase. First, ferrocene as a metal catalyst precursor containing Fe atoms and thiophene as a promoter were introduced into a continuous flow of carrier gas in a once-through reactor whose temperature was controlled at 400°C to 700°C. A mixture of nitrogen and argon was used as the carrier gas. The flow rate of the carrier gas was 30,000sccm (standard cubic centimeter per minute). By maintaining the temperature in the flow-through reactor within the above range, the metal catalyst precursor was produced as a particulate metal catalyst. The region in which the metal catalyst was produced is referred to as the first temperature zone.

[0145] The carbon source, methane, was then released into the carrier gas stream. The metal catalyst and carbon source were fed into a second temperature zone downstream of the first temperature zone, which was temperature-controlled at 1400° C. The second temperature zone was maintained at a temperature sufficient to produce carbon nanotube aggregates.

[0146] In the second temperature zone, an electric field was generated within the temperature controlled flow reactor, which produced aggregates of MWCNTs, including ULMWCNTs. The aggregates were continuously discharged through the outlet of a flow-type reactor whose temperature was controlled at 100°C to 500°C, and the MWCNT aggregates containing ULMWCNT were collected by continuous discharge as sheet-like MWCNTs containing ULMWCNT. The obtained ULMWCNT-containing sheet-like MWCNT contains ULMWCNT and MWCNT. The obtained sheet-like MWCNT containing ULMWCNT was washed with deionized water for 10 seconds to obtain MWCNT2 containing ULMWCNT.

[0147] 2. Tensile strength The MWCNT2 containing the ULMWCNT of Example 2 was cut into a size of 5 mm x 100 mm to serve as a measurement sample, which was fixed to the gripping portion of a tensile testing device (Shimadzu Corporation, Autograph AG-IS) and subjected to a tensile test at a speed of 1 mm / min. As a result, the tensile strength was 11.3 MPa.

[0148] 3. Maximum length The maximum length was measured in the same manner as in Example 1 using MWCNT2 containing ULMWCNT, and the maximum value of the maximum length was 3500 μm.

[0149] 4. Preparation of MWCNT powder 2 containing ULMWCNT MWCNT powder 2 containing ULMWCNT was obtained in the same manner as in Example 1, except that MWCNT 2 containing ULMWCNT was used and the grinding time was changed. Grinding time: 7 minutes

[0150] 5. Measurement of angle of repose Using MWCNT powder 2 containing ULMWCNT, the angle of repose was measured in the same manner as in Example 1, and the angle of repose was found to be 60 degrees.

[0151] 6. Measurement of volume resistivity Using MWCNT powder 2 containing ULMWCNT, the volume resistivity was measured in the same manner as in Example 1. As a result, the volume resistivity was 5.0 × 10 at 20 kN. -3 The value was Ω·cm.

[0152] Example 3 1. Preparation of MWCNT powder 3 containing ULMWCNT MWCNT powder 3 containing ULMWCNT was obtained in the same manner as in Example 1, except that MWCNT 2 containing ULMWCNT was used and the grinding time was changed. Grinding time: 10 minutes

[0153] 2. Measurement of angle of repose Using MWCNT powder 3 containing ULMWCNT, the angle of repose was measured in the same manner as in Example 1, and the angle of repose was found to be 45 degrees.

[0154] 3. Measurement of volume resistivity Using MWCNT powder 3 containing ULMWCNT, the volume resistivity was measured in the same manner as in Example 1. As a result, the volume resistivity was 5.2 × 10 at 20 kN. -3 The value was Ω·cm.

[0155] Comparative Example 1 1. MWCNT4 Preparation As MWCNT4, "multi-walled carbon nanotubes" (catalog number: FT7000, manufactured by C-nano Corporation) were prepared.

[0156] 2-1. Preparation of Dispersion 4 Dispersion liquid 4 was obtained in the same manner as in Example 1 using MWCNT4.

[0157] 2-2. Tensile strength The tensile strength of Dispersion 4 was measured in the same manner as in Example 1, and the result was 6.9 MPa.

[0158] 3. Maximum length The maximum length was measured in the same manner as in Example 1 using MWCNT4, and the maximum value of the maximum length was 20 μm.

[0159] 4. Preparation of MWCNT Powder 4 Using MWCNT4, MWCNT powder 4 was obtained in the same manner as in Example 1.

[0160] 5. Measurement of angle of repose The angle of repose was measured using MWCNT powder 4 in the same manner as in Example 1, and the angle of repose was found to be 60 degrees.

[0161] 6. Measurement of volume resistivity Using MWCNT powder 4, the volume resistivity was measured in the same manner as in Example 1. As a result, the volume resistivity was 2.2×10 -2 The value was Ω·cm.

[0162] Comparative Example 2 1. Preparation of MWCNT5 As MWCNT5, "multi-walled carbon nanotubes" (catalog number: FT9100, manufactured by C-nano Corporation) were prepared.

[0163] 2-1. Preparation of Dispersion 5 Dispersion liquid 5 was obtained in the same manner as in Example 1 using MWCNT5.

[0164] 2-2. Tensile strength The tensile strength of Dispersion 5 was measured in the same manner as in Example 1, and the result was 2.3 MPa.

[0165] 3. Maximum length The maximum length was measured in the same manner as in Example 1 using MWCNT5, and the maximum value of the maximum length was 15 μm.

[0166] 4. Preparation of MWCNT Powder 5 Using MWCNT5, MWCNT powder 5 was obtained in the same manner as in Example 1.

[0167] 5. Measurement of angle of repose The angle of repose was measured using MWCNT powder 5 in the same manner as in Example 1, and the angle of repose was found to be 60 degrees.

[0168] 6. Measurement of volume resistivity Using MWCNT powder 5, the volume resistivity was measured in the same manner as in Example 1. As a result, the volume resistivity was 1.7 × 10 at 20 kN. -2 The value was Ω·cm.

[0169] Comparative Example 3 1. Preparation of MWCNT6 As MWCNT6, "multi-walled carbon nanotubes" (catalog number: FT6120, manufactured by C-nano Corporation) were prepared.

[0170] 2-1. Preparation of Dispersion 6 Dispersion liquid 6 was obtained in the same manner as in Example 1 using MWCNT6.

[0171] 2-2. Tensile strength The tensile strength of Dispersion 6 was measured in the same manner as in Example 1, and the result was 8.2 MPa.

[0172] 3. Maximum length The maximum length was measured in the same manner as in Example 1 using MWCNT6, and the maximum value of the maximum length was 250 μm.

[0173] 4. Preparation of MWCNT Powder 6 Using MWCNT6, MWCNT powder 6 was obtained in the same manner as in Example 1.

[0174] 5. Measurement of angle of repose The angle of repose was measured in the same manner as in Example 1 using MWCNT powder 6, and the angle of repose was found to be 55 degrees.

[0175] 6. Measurement of volume resistivity Using MWCNT powder 6, the volume resistivity was measured in the same manner as in Example 1. As a result, the volume resistivity was 1.5×10 -2 The value was Ω·cm.

[0176] The above results are shown in Table 1.

[0177] [Table 1]

[0178] It was confirmed that the multi-walled carbon nanotube powders obtained in Examples 1 to 3 were pulverized multi-walled carbon nanotubes having a tensile strength of 10 MPa to 100 MPa and an angle of repose of 10 degrees to 90 degrees. The multi-walled carbon nanotube powders obtained in Examples 1 to 3 had a volume resistivity of 5.0×10 -3 Ω cm~9.2×10 -3 Ω cm, 5.0×10 -2 Since the resistivity is Ω·cm or less, both are conductive additives with excellent conductivity improving effects.

Claims

1. The conductive assistant comprises a powder of multi-walled carbon nanotubes which is a pulverized product of multi-walled carbon nanotubes having a tensile strength of 10 MPa to 100 MPa and has an angle of repose of 10 degrees to 90 degrees.

2. The conductive assistant according to claim 1, wherein the multi-walled carbon nanotubes have a maximum length of 10 μm to 30,000 μm.

3. The conductive assistant according to claim 1 or 2, which is a conductive assistant for a negative electrode.

4. A dispersion comprising the conductive assistant according to claim 1 or 2 and a dispersion medium.

5. An electrode comprising an electrode active material and the conductive assistant according to claim 1 or 2.

6. A secondary battery comprising the electrode according to claim 5 .

7. The multi-walled carbon nanotube powder is a pulverized product of multi-walled carbon nanotubes having a tensile strength of 10 MPa to 100 MPa and a maximum length of 1,000 μm to 30,000 μm, and has an angle of repose of 10 degrees to 90 degrees.

8. A planar aggregate comprising the multi-walled carbon nanotube powder according to claim 7.

9. A filter using the planar assembly according to claim 8.

10. 9. An electromagnetic wave shield using the planar assembly according to claim 8.

11. A pellicle for extreme ultraviolet rays using the planar assembly according to claim 8.

Citation Information

Patent Citations

  • Method for purifying carbon nanotube

    JP1996231210A

  • Manufacturing and application of nanofiber ribbons and sheets, as well as twisted and untwisted nanofiber yarns.

    JP2008523254A

  • Electromagnetic wave shielding material and manufacturing method therefor

    JP2009277736A

  • Air purification filter, manufacturing method of air purification filter, air cleaning machine and cleaner

    JP2017051384A

  • Producing method of pellicle self-supporting film, producing method of pellicle, and producing method of semiconductor device

    JP2020160345A

Cited By

  • Carbon nanotube aggregates, conductive materials, electrodes, secondary batteries, planar aggregates, laminates, filters, electromagnetic shielding, pellicles for extreme ultraviolet radiation, and methods for measuring mean curvature.

    JP2026164685A

  • Carbon nanotube aggregates, conductive materials, electrodes, secondary batteries, planar aggregates, laminates, filters, electromagnetic shielding, pellicles for extreme ultraviolet radiation, and methods for measuring mean curvature.

    JP2026164686A

  • Carbon nanotube aggregate, conductive material, electrode, secondary battery, planar aggregate, laminate, filter, electromagnetic wave shield, pellicle for extreme ultraviolet rays, and method for measuring mean curvature

    JP7785235B1